Bilateral intra-lymph node Warthin's tumor as a potential diagnostic pitfall mimicking metastatic carcinoma - Santos-Sousa, Ana Lívia [UNESP]; Camilo-Júnior, Deolino João; Conrado-Neto, Sebastião [UNESP]; Bernabé, Daniel Galera [UNESP]; Xavier-Júnior, Jose Candido C. (Wiley, 2024)
Warthin's tumor (WT) is a benign and frequent salivary gland tumor primarily affecting the parotid gland. In some cases, this tumor can involve the extra parotid region and affect cervical lymph nodes. Fine-needle aspiration can be the first step in the diagnostic approach to lymphadenopathy; however, specimens from intra-nodal WT can present a potential pitfall, leading to a misdiagnosis of metastasis. Here, we report an unusual case of a patient with bilateral WT in parotid lymph nodes misdiagnosed as metastases. In addition, we highlight the cytopathological aspects of WT to alert cytopathologists about this challenging diagnosis.
Keywords: fine-needle aspiration; lymphatic metastasis; salivary gland neoplasms; Warthin tumor